The influence of substitution decisions made by national team coaches on final match outcomes at UEFA EURO 2024 - Gabrys, T.; Chruscinski, R.; Garnys, M.; Suva, M.; Švátora, K. (Frontiers in Sports and Active Living, 2025)
Introduction: Coaches leading national football teams during championship tournaments make decisions about tactical substitutions of players in critical match phases. This may be an attempt to change or defend a favorable score. This study focused on the time of decision-making of forced and planned substitutions, considering its characteristics: neutral, offensive, and defensive. The point of analysis of the substitutions was the match outcomes at the time of the substitutions and the final result and impact of the substitution concerning the result.